2018
DOI: 10.1007/s11606-018-4374-1
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Perspectives Regarding Prescription Drug Monitoring Program Use Within the Department of Veterans Affairs: a Multi-State Qualitative Study

Abstract: Despite the time and administrative burdens associated with their use, VA physicians in our study broadly supported PDMPs. The application of our findings to ongoing PDMP implementation efforts may strengthen PDMP use both within and outside VA and improve the safe prescribing of opioids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 17 publications
1
38
2
1
Order By: Relevance
“…Although 30% of the patients seen in outpatient medicine had acute pain, the PDMP was accessed in that setting only 16% of the time. Overall, our results are consistent with other studies that describe low PDMP utilization rates despite reports by providers recognizing that the PDMP is an important clinical tool 12‐15 …”
Section: Discussionsupporting
confidence: 92%
“…Although 30% of the patients seen in outpatient medicine had acute pain, the PDMP was accessed in that setting only 16% of the time. Overall, our results are consistent with other studies that describe low PDMP utilization rates despite reports by providers recognizing that the PDMP is an important clinical tool 12‐15 …”
Section: Discussionsupporting
confidence: 92%
“…VA physicians noted that incomplete or unavailable data was a significant barrier to increasing PDMP use. 409 In 2016, HHS issued a policy requiring IHS prescribers to query the PDMP before prescribing opioids and pharmacists to report their dispensing activity to the PDMP; it also directed IHS to ensure that memorandums of understanding were signed with the appropriate state offices. 49,410 Links to and use of PDMPs varies across IHS service areas.…”
Section: Prescription Drug Monitoring Programsmentioning
confidence: 99%
“… 27 Enforcement may also be limited by implementation barriers such as limited resources. 27 Qualitative research has identified some key factors influencing implementation of PDMPs such as linkage to electronic health records (EHR), 29 - 31 and communication barriers between physicians and pharmacists. 32 , 33 In addition, qualitative research has illuminated the perceived unintended consequences of the PDMP by PDMP staff, law enforcement officials, and administrative agency employees.…”
Section: Introductionmentioning
confidence: 99%